2017
DOI: 10.1007/s00412-017-0633-x
|View full text |Cite
|
Sign up to set email alerts
|

Using human artificial chromosomes to study centromere assembly and function

Abstract: Abstract:Centromeres are the site of assembly of the kinetochore, which directs chromosome segregation during cell division. Active centromeres are characterized by the presence of nucleosomes containing CENP-A and a specific chromatin environment that resembles that of active genes. Recent work using Human Artificial Chromosomes (HAC) sheds light on the fine balance of different histone post-translational modifications and transcription that exists at centromeres for kinetochore assembly and maintenance. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 180 publications
(219 reference statements)
0
34
0
Order By: Relevance
“…Consistent with a global shut-down of transcription during prometaphase (the physiological equivalent of nocodazole-arrested cells), RNA Polymerase II is generally found displaced from chromatin ( Hsiung et al, 2016 ), with the notorious exception of the centromeric region ( Chan et al, 2012 ). Because recent studies have suggested that non-coding RNAs associate with centromere and kinetochore proteins, including CENP-A, CENP-C and Aurora B ( Blower, 2016 ; Carone et al, 2009 ; Du et al, 2010 ; Ferri et al, 2009 ; Molina et al, 2017 , 2016 ; Rošić et al, 2014 ; Wong et al, 2007 ), it is possible that transcription of non-coding RNAs plays a role in centromere assembly and function. However, whether this occurs during mitosis or during G1, when centromere assembly takes place in mammalian cells ( Jansen et al, 2007 ) remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with a global shut-down of transcription during prometaphase (the physiological equivalent of nocodazole-arrested cells), RNA Polymerase II is generally found displaced from chromatin ( Hsiung et al, 2016 ), with the notorious exception of the centromeric region ( Chan et al, 2012 ). Because recent studies have suggested that non-coding RNAs associate with centromere and kinetochore proteins, including CENP-A, CENP-C and Aurora B ( Blower, 2016 ; Carone et al, 2009 ; Du et al, 2010 ; Ferri et al, 2009 ; Molina et al, 2017 , 2016 ; Rošić et al, 2014 ; Wong et al, 2007 ), it is possible that transcription of non-coding RNAs plays a role in centromere assembly and function. However, whether this occurs during mitosis or during G1, when centromere assembly takes place in mammalian cells ( Jansen et al, 2007 ) remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The HAC loss rate is roughly 10-fold higher when compared with the native chromosomes (Nakano et al 2008), making the assay very sensitized and allowing a statistically significant number of events in a realistic sample size when studying the CIN phenotype in human cells. Previously, the HAC was used for low-throughput identification of drugs that elevate chromosome instability (CIN) in cancer cells (Lee et al 2013aKim et al 2016), as a gene delivery vector for the efficient and regulated expression of exogenous full-length genes in mammalian cells (Iida et al 2010;Kim et al 2011;Kouprina et al 2012Kouprina et al , 2013Kouprina et al , 2014Kononenko et al 2014;Liskovykh et al 2015;Lee et al 2018), and for studies of the epigenetic regulation of human kinetochores (Bergmann et al 2012;Ohzeki et al 2015;Molina et al 2017).…”
Section: Experimental System To Identify Novel Human Genes Controllinmentioning
confidence: 99%
“…This assay is based on a nonessential human artificial chromosome (HAC) expressing a short half-life green fluorescent protein (GFP). This HAC, like other HACs, follows the rules of mitosis and chromosome segregation just like the natural chromosomes during the cell cycle progression (Nakano et al 2008;Bergmann et al 2012;Ohzeki et al 2015;Molina et al 2017). It is worth noting that the use of yeast artificial chromosomes (YACs) was critical for the discovery and systematic analysis of CIN genes in S. cerevisiae (Maine et al 1984;Spencer et al 1990;Kouprina et al 1993;Roberts et al 1994).…”
mentioning
confidence: 99%
“…Consistent with a global shut-down of transcription during prometaphase (the physiological equivalent of nocodazole-arrested cells), RNA Polymerase II is generally found displaced from chromatin (Hsiung et al, 2016), with the notorious exception of the centromeric region (Chan et al, 2012). Because recent studies have suggested that non-coding RNAs associate with centromere and kinetochore proteins, including CENP-A, CENP-C and Aurora B (Blower, 2016;Carone et al, 2009;Du et al, 2010;Ferri et al, 2009;Molina et al, 2017;Molina et al, 2016;Rošić et al, 2014;Wong et al, 2007), it remains possible that transcription of non-coding RNAs plays a role in centromere assembly and function. However, whether this occurs during mitosis or during G1, when centromere assembly takes place in mammalian cells (Jansen et al, 2007) is unclear.…”
Section: Discussionmentioning
confidence: 89%